Micro-ANP Network Protocol Architecture and Simulation Implementation - DU Xiujuan; LAN Shenglin; LIU Fan; FENG Zhenxing (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Due to the unique characteristics of underwater sensor network (UWSN), conventional network protocols for terrestrial WSN are unable to satisfy the performance of UWSN. In addition, the limits of energy, CPU and memory of UWSN nodes demand the protocol stack running on them should be simple and efficient. The paper proposed a Micro-ANP protocol architecture model for UWSN, which are three layered including application layer, network-transport layer and physical layer, optimized packet size using three objective functions: packet throughput, energy consumption and resource consumption under Micro-ANP architecture by means of MATLAB, designed and implemented UWSN simulation platform based on Micro-ANP and QualNet software, lay a solid foundation for further research on underwater sensor network. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2328